Potencialidades e dilemas da participação de agricultores familiares em uma metodologia de experimentação participativa para o desenvolvimento rural sustentável: um estudo de caso - Guyot, Marina Souza Dias (2009)
In order to surpass the challenges of the Sustainable Agricultural Development initiatives where the popular participation is recognized as vital have been undertaken. However, the effectiveness of this participation varies and this changeability is related, among other factors, to the used methodologies. The objective of this research was to describe and to analyze the potentialities and quandaries of the participation of familiar farmers in the .Sustainable Agricultural Development. The participatory experimentation methodology applied is the one proposed by the project Experimentation in Agrossilviculture and Social Participation developed in the City of Joanópolis/SP. The research was carried through semi structured interviews with participant this project s farmers as well as through participant observation. The data have been systemized through re-readings, reductions and establishments of standards. Then, the data analysis was held on through the dialogue between the collected information and consulted bibliography. It was observed that the potentialities of the participation of familiar agriculturists in the Sustainable Agricultural Development are related to the search for better conditions of life. The identified quandaries allude to the lack of participation exercise both by the institutions that act with these farmers, as for themselves. It was identified that the methodology of participatory experimentation favors the participation of the family farmers in the Sustainable Agricultural Development, once it places them in the position of crucial agents of the process.